THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND NUTRITIONAL STATUS AND QUALITY OF LIFE AMONG ADOLESCENTS IN BOLAANG MONGONDOW REGENCY - Dewi, Citra Kumala (International Journal of Social Science, 2025)
Adolescents’ quality of life is an important indicator of overall health status, encompassing physical, psychological, social, and environmental dimensions. Physical activity and nutritional status are commonly associated with adolescent health; however, their relationship with quality of life remains inconsistent across studies. This study aimed to analyze the relationship between physical activity and nutritional status and adolescents’ quality of life in Bolaang Mongondow Regency. This study employed an observational analytic design with a cross-sectional approach, conducted among junior and senior high school adolescents in Bolaang Mongondow Regency in October 2023. A total of 406 adolescents were selected using cluster random sampling. Physical activity was assessed using the Global School-based Health Survey (GSHS) questionnaire, nutritional status was determined using Body Mass Index-for-Age (BMI-for-age), and quality of life was measured using the WHOQOL-BREF instrument. Data were analyzed using univariate and bivariate analyses with the Chi-square test at a 95% confidence level. The results showed that there was no significant relationship between physical activity and adolescents’ quality of life across all quality of life domains (p > 0.05). Similarly, nutritional status was not significantly associated with adolescents’ quality of life (p > 0.05). These findings indicate that variations in physical activity levels and nutritional status do not necessarily influence adolescents’ perceived quality of life. In conclusion, physical activity and nutritional status are not significantly associated with adolescents’ quality of lifein Bolaang Mongondow Regency. Adolescents’ quality of life may be more strongly influenced by psychosocial and environmental factors that were not examined in this study. Future research is recommended to incorporate these factors to obtain a more comprehensive understanding of adolescents’ quality of life.